The Impact of the QRIS Payment System on Increasing the Net Profit Margin of MSMEs in Bekasi Regency - Dian Indah Sari; Slamet Maryoso (Cita konsultindo, 2025)
Abstract The purpose of this study was to evaluate the effect of the QRIS payment system on the growth of the Net Profit Margin of MSMEs in Bekasi Regency. The study population consisted of MSMEs that have used QRIS in the area. A purposive sampling method was used for sampling. Data were collected by distributing questionnaires to 50 MSME owners. Data processing was performed using SPSS 21 software. Multiple linear regression was used for data analysis. The study concluded that the QRIS payment system has a positive impact on increasing the Net Profit Margin of MSMEs ;located in Bekasi Regency. The use of QRIS offers benefits to MSMEs in the regency, such as a practical and fast method, requiring only one QR code, reducing reliance on cash, automating transaction recording, and enhancing the image and credibility of MSMEs. With the implementation of QRIS, the Net Profit Margin of MSMEs in Bekasi Regency has increased due to the fast and practical transaction process, operational cost savings, market expansion, increased consumer trust, transparency and ease of transaction reporting, and more secure transactions. Keywords: Payment System, QRIS, Net Profit Margin, MSMEs